1999
DOI: 10.1590/s0001-37141999000200003
|View full text |Cite
|
Sign up to set email alerts
|

Toxic metabolites from culture filtrate of Fusarium oxysporum and its effects on cucumber cells and plantlets

Abstract: Resistance of cucumber plantlets to culture filtrate of Fusarium oxysporum is correlated with resistance of single cells from callus. Single cells and plantlets of two cultivars of cucumber were incubated with culture filtrates. Rapid cell death occurred, as assessed by the stain fluorescein diacetate. More cell death ocurred in the cells of the cultivar Aodai than in to cells of the cultivar Caipira, which presented high level of resistance. Maximum toxic activity of culture filtrates was attained after 21-25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…The Czapeck-dox liquid medium, which is chemically defined, was suitable for stimulating the production of this type of metabolite produced by Fusarium, in accordance with reports by other investigators (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The Czapeck-dox liquid medium, which is chemically defined, was suitable for stimulating the production of this type of metabolite produced by Fusarium, in accordance with reports by other investigators (18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 85%
“…The metabolic extracts were obtained based on the protocol of Melo and Piccinin (18). The fungus was transferred to Petri dishes containing potatodextrose agar (Difco, USA) culture medium.…”
Section: Microorganisms and Culture Conditionsmentioning
confidence: 99%
“…At harvesting, the mycelium mat was removed from the filtrate and further filtered with using Whatman 03 mm filter paper. The broth cultures were then filter sterilized through a millipore filter (pore diameter of 0.2 μm) [ 52 ]. The culture filtrate toxic metabolites from were further used for histopathological tests.…”
Section: Methodsmentioning
confidence: 99%
“…Hernandes et al [ 41 ] demonstrated that filtered Fusarium oxysporum extract induced an inflammatory reaction and programmed cell death in rat skin. Similarly, de Melo and Piccinin [ 42 ] reported the toxic activity of F. oxysporum where the fungal culture extracts provoked reactions that produced withering in cucumber cells and plantlets, leading to cell death.…”
Section: Major Fusarium Disease Determinants: Mmentioning
confidence: 99%